2009
DOI: 10.3174/ajnr.a1853
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Experimental Intracranial Aneurysm Models: A Systematic Review

Abstract: SUMMARY: Animal models are necessary to develop and test innovations in aneurysm therapy before clinical introduction. This review aims at identifying the most likely candidates for standardizing preclinical testing of aneurysm devices. We systematically searched electronic databases for publications on animal aneurysm models from 1961-2008 to assess the methodologic quality of the studies and collect data on the patency and angiographic and pathologic outcomes of treatments. There has been a steady increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 49 publications
1
67
0
Order By: Relevance
“…Even though data from an animal model cannot be transferred to humans without restrictions (eg, that peripheral swine vessels might be less susceptible to perforations compared with human cerebral vessels or that our swine model did not allow detection of thrombotic emboli), swine represent an established animal model for endovascular procedures, given their comparable vascular anatomy and coagulation. 28 To anticipate differences between humans and swine, we examined coil retrieval in vessels that are comparable with affected human vessels with regard to size, blood flow, and accessibility. A further limitation is that an experiment that involves all possible combinations of coils, vessels, and stent retrievers is practically impossible.…”
Section: Limitationsmentioning
confidence: 99%
“…Even though data from an animal model cannot be transferred to humans without restrictions (eg, that peripheral swine vessels might be less susceptible to perforations compared with human cerebral vessels or that our swine model did not allow detection of thrombotic emboli), swine represent an established animal model for endovascular procedures, given their comparable vascular anatomy and coagulation. 28 To anticipate differences between humans and swine, we examined coil retrieval in vessels that are comparable with affected human vessels with regard to size, blood flow, and accessibility. A further limitation is that an experiment that involves all possible combinations of coils, vessels, and stent retrievers is practically impossible.…”
Section: Limitationsmentioning
confidence: 99%
“…21 In general, arterial sidewall aneurysm models cannot predict the ability of new coils to improve long-term angiographic results under more challenging hemodynamic conditions. 6 For example, it was shown by computer-assisted morphometric comparison of various aneurysm models that bare platinum coils performed equally as well as HydroCoils (MicroVention Terumo, Aliso Viejo, California) only in a canine arterial sidewall aneurysm model, while in arterial bifurcation models, HydroCoils provided better long-term stable occlusion. 18 In contrast, the venous pouch arterial bifurcation model is created by a venous pouch sutured into an artificial true bifurcation of both CCAs.…”
Section: Discussionmentioning
confidence: 99%
“…The postulated main advantages of this model are true bifurcational hemodynamics 21 and the possibility of varying the anatomy of the bifurcation and neck/fundus size of the aneurysm. 6 The postulated histomorphologic drawback is a supposed pronounced foreign body reaction around the suture lines at the neck plane, impairing thrombus organization and fibrovascular healing. 10 However, it has already been shown that the foreign body response to the monofilament sutures around the anastomosis is only benign and that this chronic inflammatory reaction to nonresorbable sutures is locally confined to the outer parts of the respective vessel walls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations